P0540EFFECT OF MEMBRANE MATERIALS ON VANCOMYCIN, TEICOPLANIN AND LINEZOLID REMOVAL DURING CONTINUOUS RENAL REPLACEMENT THERAPIES: AN IN VITRO STUDY. (6th June 2020) - Godi, Llaria; Lorenzin, Anna; De Cal, Massimo; Ronco, Claudio
Abstract: Background and Aims: In a continuous renal replacement therapy (CRRT) scenario, removal of anti-methicillin resistant Staphylococcus Aureus agents can be quantitatively important, thereby contributing to clinically relevant decreases in their plasma concentration during treatment. Extracorporeal elimination of antimicrobial agents is influenced by the dose and modality prescribed, as well as the sieving coefficient (SC) and adsorptive properties of the membrane used.The aim of this study was to document the specific SC and adsorptive capacity of three different membrane materials related to vancomycin, teicoplanin and linezolid. Method: This in vitro study used a model of continuous veno-venous hemofiltration. 500 ml of whole blood from healthy donor spiked with one antibiotic under investigation was pumped (blood flow of 50 ml/min and ultrafiltrate flow of 10 ml/min) in a closed-circuit using polysulfone (PS), polymethylmethacrylate (PMMA) and polyacrylonitrile (PAN) membranes. Samples were collected from in-flow, out-flow and ultrafiltrate lines in a 360 min period. Antibiotic concentrations were measured to calculate SCs. Mass balance analysis was assessed to evaluate the adsorptive capacity of PS, PMMA and PAN membrane related to each antibiotic. Results: The SCs were substantially affected by the hemodialyzers material in the case of Vancomycin, where PMMA membrane had higher SC (SC=0.89±0.01) compared to PAN (SC=0.79±0.02) and PS (SC=0.62±0.03) membranes. The effect of material was minor for Teicoplanin (Sc=0.12±0.05 for PS, Sc=0.17±0.05 for PMMA, Sc=0.19±0.00 for PAN) and no noticeable difference within hemodialyzers was found for Linezolid (Sc=0.92±0.03 for PS, Sc=0.95±0.01 for PMMA, Sc=0.95±0.00 for PAN). In terms of adsorptive capacity, PS and PMMA membranes showed higher interaction with Vancomycin and Teicoplanin compared with PAN membrane, while a small amount of Linezolid was adsorbed by all the three filters. The cumulative adsorbed amount of PS and PMMA of Teicoplanin were also clinically relevant (99.15 mg/m2 and 51.33 mg/m2 respectively) compared to PAN membrane (9.14 mg/m2). Conclusion: PS, PMMA and PAN membranes behave differently in terms of sieving and adsorptive properties related to vancomycin, teicoplanin and linezolid. These differences may have a clinical influence on vancomycin and teicoplanin removal during CRRT, while linezolid variability during CRRT hasn't to be ascribed for membrane material.